Syndromes of production and tree-cover dynamics of Neotropical grazing land. Issue 4 (21st April 2019) - Valencia Mestre, Mariana C.; Ferguson, Bruce G.; Vandermeer, John
ABSTRACT: This paper provides a conceptual framework for analyzing the dynamics of tree cover transformations in the cattle pastures across the Neotropics. It proposes that tree cover variability across cattle pastures can be envisioned as a set of 'syndromes of production, ' among which transformations may be linear, non-linear, or multivalued. Our framework is informed by a review of the literature from which we define the components that make up tree cover and the socioecological drivers of tree cover in cattle pastures. We propose that the drivers of tree cover are the continuum between two economies: the peasant and the capitalist.